Pengembangan Aplikasi Math Mobile Learning “Smartline” Menggunakan Adobe Animate pada Materi Garis dan Sudut Di Tingkat SMP - Mohammad Zulfa Ainun Niam; Nanang Nabhar Fakhri Auliya (ARITHMETIC: Academic Journal of Math, 2022)
This study aims to design, develop, and produce media products in the form of math mobile learning applications assisted by Adobe Animate software about lines and angles that meet the criteria of validity and media practicality so that the media can be applied in the learning process of lines and angles. The type of research used is research and development (Research and Development) which refers to the ADDIE model. The stages of developing this model include Analysis, Design, Development, Implementation, and Evaluation. 35 students of class VII MTs NU Raudlatus Shibyan were the subjects of this study. The data collection instruments were material expert validation sheets, media experts, and user response questionnaire sheets. The results of the development research are: (1) the results of the validation of material experts and media experts produce media validity in the "Very Valid" category and a validity score of 82.5 and 83.5 respectively; (2) the results of limited trials and the field gave results of "Very Practical" in the practicality category and the scores were respectively 85.2 and 85.43333333. Based on the validity and practicality scores of the media, the learning media in the form of a mobile learning math application using Adobe Animate software is feasible to be applied as a learning media for class VII mathematics about lines and angles.